Analisis Ciri Frasa Endosentris dalam Bahasa Madura pada Koran Madura Satu Hati untuk Bangsa - Khoirun Nadia; Irfan Kholid Sofhan; Rintan Amalia Rohar; Hasan Suaedi (Universitas Palangka Raya, 2025)
This study examines the characteristics of endocentric phrases in the Madurese language as used in the newspaper Madura Satu Hati Untuk Bangsa. The primary focus of the research is to identify the types of endocentric phrases and their formation patterns. This study is significant because the Madurese language, as one of Indonesia's cultural treasures, has unique syntactic characteristics that need to be understood to support its preservation and development. Using a qualitative descriptive method, the research data were collected from news articles, opinion pieces, and other columns in the newspaper. The analysis was conducted based on structural linguistic theory, which emphasizes the relationships between the elements forming phrases. The results show that endocentric phrases in the Madurese language can be classified into two main types: coordinative phrases and attributive phrases. The formation patterns of endocentric phrases reflect a unique combination of free and bound morphemes, as well as grammatical structures that demonstrate harmony between the head and its modifiers. The study found that the characteristics of endocentric phrases in Madurese display certain similarities and differences with Indonesian, particularly in grammar and word order. The findings of this study not only enrich the linguistic documentation of the Madurese language but also provide valuable insights for the broader development of regional language studies.